Dari Arab ke Nusantara: Pengaruh bahasa dan sastra arab dalam pembentukan budaya pada kerajaan-kerajaan di Aceh, Sulawesi, dan Jawa - Renata, Ririn (Maliki Interdisciplinary Journal, 2025)
This research discuccec the role of Arabic language and Arabic literature in cultural development, especially in the kingdooms in Aceh, Sulawesi and Jawa. Starting from pre-Islamic to modern era. This research aims to identify the process of the entry of Arabic language and literature into Indonesia and analyze its contribution to culture. Through the analysis of various works, especially Arabic language and literature, this article reveals how it became an important medium in the spread of Islam and the formation of culture in the kingdoms of Aceh, Sulawesi and Java. In the cultural aspect, Arabic language and literature have contributed tu the development of Indonesian culture, such as the use of Arabic proper names and the archipelago, wich believed in cultural expression and strengthened the Islamic identity of the community. Arabic literature not only functions as an aesthetic expression, but also as an instrument to maintain and strengthen Islamic values in facing the challenges of modernity. This study confirms that Arabic language and literature are important components in the process of Islamization and the formation of local civilization in the archipelago